B Cell Intrinsic Mechanisms Constraining IgE Memory - Laffleur, Brice; Debeaupuis, Orianne; Dalloul, Zeinab; Cogné, Michel (Frontiers in Immunology, 2017)
Memory B cells and long-lived plasma cells are key elements of adaptive humoral immunity. Regardless of the immunoglobulin class produced, these cells can ensure long-lasting protection but also long-lasting immunopathology, thus requiring tight regulation of their generation and survival. Among all antibody classes, this is especially true for IgE, which stands as the most potent, and can trigger dramatic inflammatory reactions even when present in minute amounts. IgE responses and memory crucially protects against parasites and toxic components of venoms, conferring selective advantages and explaining their conservation in all mammalian species despite a parallel broad spectrum of IgE-mediated immunopathology. Long-term memory of sensitization and anaphylactic responses to allergens constitute the dark side of IgE responses, which can trigger multiple acute or chronic pathologic manifestations, some punctuated with life-threatening events. This Janus face of the IgE response and memory, both necessary and potentially dangerous, thus obviously deserves the most elaborated self-control schemes.